2015
DOI: 10.1017/s000711451500118x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of dietary fatty acids on FFA1 and FFA4 and characterisation of pinolenic acid as a dual FFA1/FFA4 agonist with potential effect against metabolic diseases

Abstract: Various foods are associated with effects against metabolic diseases such as insulin resistance and type 2 diabetes; however, their mechanisms of action are mostly unclear. Fatty acids may contribute by acting as precursors of signalling molecules or by direct activity on receptors. The medium-and long-chain NEFA receptor FFA1 (free fatty acid receptor 1, previously known as GPR40) has been linked to enhancement of glucose-stimulated insulin secretion, whereas FFA4 (free fatty acid receptor 4, previously known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 67 publications
3
111
0
Order By: Relevance
“…138,139 Although the current consensus appears to be that FFA1 is not responsible for the detrimental chronic effects of LCFA exposure, recent studies have continued to suggest FFA1 may play some role in lipotoxic effects of LCFAs. 140−142 One possible explanation could be, given the diversity of LCFAs known to activate FFA1, that efficacy differences reported among LCFAs, 129 or perhaps even signaling bias in their effects at FFA1, could account for these discrepancies. The concept of signaling bias in GPCRs with multiple endogenous ligands is not unusual and, indeed, has been widely reported within the chemokine receptor family.…”
Section: Lcfas At Ffa1mentioning
confidence: 99%
See 1 more Smart Citation
“…138,139 Although the current consensus appears to be that FFA1 is not responsible for the detrimental chronic effects of LCFA exposure, recent studies have continued to suggest FFA1 may play some role in lipotoxic effects of LCFAs. 140−142 One possible explanation could be, given the diversity of LCFAs known to activate FFA1, that efficacy differences reported among LCFAs, 129 or perhaps even signaling bias in their effects at FFA1, could account for these discrepancies. The concept of signaling bias in GPCRs with multiple endogenous ligands is not unusual and, indeed, has been widely reported within the chemokine receptor family.…”
Section: Lcfas At Ffa1mentioning
confidence: 99%
“…For example, analysis of the widest group of fatty acids yet reported found that nearly all MCFAs and LCFAs tested had potencies falling within the range of 1−20 μM, and indeed, even the SFAs, which typically have not been associated with FFA4 agonism, have comparable potency to the n−3 PUFAs at FFA4. 129 However, it must be noted that although the potency does appear to be broadly similar across the MCFAs and LCFAs, efficacy differences among the fatty acids are apparent.…”
Section: Lcfas At Ffa4mentioning
confidence: 99%
“…Oleic acid and palmitoleic acid activate both FFA4 and FFA1, with palmitoleic acid being 5-to 10-fold more potent on FFA4 (Table 1) (18,43). Interestingly, the endogenous synthesis of palmitoleic acid has been connected to FFA4 through regulation of SCD1/ 9D (48).…”
Section: Monounsaturated Fatty Acidsmentioning
confidence: 99%
“…This is interesting in light of the fact that LA and n-6 fatty acids have been viewed as predominantly proinflammatory. ALA and LA are both among the most potent fatty acids on FFA1 and FFA4 ( Table 1) (9,18,43,50,59), which is notable because of their abundance in diet.…”
Section: Plant-derived Essential Fatty Acids: Linoleic Acid and α-Linmentioning
confidence: 99%
See 1 more Smart Citation